Soil macrofauna density and diversity across a chronosequence of tropical forest restoration in Southeastern Brazil - Amazonas,N. T. (2018)
Abstract Edaphic macrofauna must be better studied if we want to take advantage of their full potential for the restoration of tropical ecosystems. We investigated changes in edaphic macrofauna density and diversity along a secondary succession chronosequence in the Atlantic Forest. Our results show some clear patterns of change in soil macrofauna along the chronosequence. Density did not increase along secondary succession, but was correlated with canopy cover. Diversity was characterized by high dominance of social insects and evenness among other groups. We conclude soil macrofauna has a high capacity to recolonize young forests and that its recovery is considerably fast compared to other ecosystem transformations.